2019
DOI: 10.3847/1538-3881/ab21e1
|View full text |Cite
|
Sign up to set email alerts
|

The Swift UVOT Stars Survey. III. Photometry and Color–Magnitude Diagrams of 103 Galactic Open Clusters

Abstract: As part of the Swift/UVOT Stars Survey, we present near-ultraviolet (3000-1700 A) point-source photometry for 103 Galactic open clusters. These data, taken over the span of the mission, provide a unique and unprecedented set of near-ultraviolet point-source photometry on simple stellar populations. After applying membership analysis fueled mostly by GAIA DR2 proper motions, we find that 49 of these 103 have clear precise CMDs amenable to investigation. We compare the CMDs to theoretical isochrones and find goo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 133 publications
(143 reference statements)
1
22
0
Order By: Relevance
“…In Figure 15 the stars have been differentially coloured based on their Teff obtained by comparing the optical magnitudes with the best fitting PARSEC isochrone. We notice that the deviation of these cool stars from isochrones begins around 6500 K, which is similar to that identified by Siegel, et al (2019). These deviations from isochrones have also been noted in NUV photometry of cool stars by Barker & Paust (2018).…”
Section: Uv Emissionsupporting
confidence: 85%
See 4 more Smart Citations
“…In Figure 15 the stars have been differentially coloured based on their Teff obtained by comparing the optical magnitudes with the best fitting PARSEC isochrone. We notice that the deviation of these cool stars from isochrones begins around 6500 K, which is similar to that identified by Siegel, et al (2019). These deviations from isochrones have also been noted in NUV photometry of cool stars by Barker & Paust (2018).…”
Section: Uv Emissionsupporting
confidence: 85%
“…Several cool stars deviate from the single star isochrones in the UVW1-UVW2 CMD as shown in the Figure 15. Siegel, et al (2019) had also identified this strange feature in the UVW2-UVW1 CMDs of a few star clusters. They had suggested that this feature could be due to red leak in UVW1 and UVW2 filters or deficiencies in the underlying atmosphere models.…”
Section: Uv Emissionmentioning
confidence: 90%
See 3 more Smart Citations